2018
DOI: 10.1177/1354856518770987
|View full text |Cite
|
Sign up to set email alerts
|

m-Reading: Fiction reading from mobile phones

Abstract: Mobile phones are reportedly the most rapidly expanding e-reading device worldwide. However, the embodied, cognitive and affective implications of smartphone-supported fiction reading for leisure (m-reading) have yet to be investigated empirically. Revisiting the theoretical work of digitization scholar Anne Mangen, we argue that the digital reading experience is not only contingent on patterns of embodied reader–device interaction (Mangen, 2008 and later) but also embedded in the immediate environment and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
(117 reference statements)
0
19
0
1
Order By: Relevance
“…Individuals may prefer print for lengthier texts and when they want to concentrate (Baron, 2017) but would rather use their phones to search for instant information (Zasacka, 2017). Reading on a phone also provides alternative sources of reading materials otherwise not available in print (Kuzmičová, Schilhab, & Burke, 2018).…”
Section: Reading Print and Digital Booksmentioning
confidence: 99%
“…Individuals may prefer print for lengthier texts and when they want to concentrate (Baron, 2017) but would rather use their phones to search for instant information (Zasacka, 2017). Reading on a phone also provides alternative sources of reading materials otherwise not available in print (Kuzmičová, Schilhab, & Burke, 2018).…”
Section: Reading Print and Digital Booksmentioning
confidence: 99%
“…Contemporary advances in e‐publishing and portable technology seem to promise a future where people will learn through reading anytime, anywhere. While the potential worth of mobile practices for informal learning (Tseloudi and Arnedillo‐Sánchez, ) and leisure reading (Kuzmičová et al, In Press; see also next section) is relatively evident, institutionalised learning behaviour may not adapt as easily. Exploratory research has shown student samples, internationally, to resist abandoning traditional print formats for study purposes (Baron et al, ; Fortunati and Vincent, ).…”
Section: Reading Environments Embodied and Socialmentioning
confidence: 99%
“…Also, in the company of friends, reading on the phone was reported more acceptable than print reading, due to the tacit assumption that the former will be quick and superficial and thus will not prevent the reader from interacting with others. Unlike single‐purpose dedicated settings, non‐dedicated public environments are versatile with respect to the bodily actions and social interactions afforded, and smartphones seem to make reading more adaptable than ever before to this versatility (Kuzmičová et al, In Press).…”
Section: Reading Environments Embodied and Socialmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the ways in which humans interact and use these technologies have attracted considerable attention in the scientific community, which has led to innovations in technology, as well as theories related to changes in technology adoption according to jurisdiction (Ricardo-Barreto et al), behavior (Mangen and Velay, 2010; Marco and Tormo-Irun), and in the human brain itself (Greenfield, 2015; Lemus-Zúñiga et al, 2015). These developments take place in the context of a rapidly aging society, and where many disciplines have struggled to address the interaction of technology with the aging process in terms of human development, cognition, social support, and emotional skills (Charness and Boot, 2009; Mangen, 2016; Kuzmičová et al, 2018).…”
mentioning
confidence: 99%